2014
DOI: 10.1371/journal.pone.0096982
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Vasculogenic Mimicry and Prolongation of Host Survival in Highly Aggressive Gallbladder Cancers by Norcantharidin via Blocking the Ephrin Type a Receptor 2/Focal Adhesion Kinase/Paxillin Signaling Pathway

Abstract: Vasculogenic mimicry (VM) is a newly-defined tumor microcirculation pattern in highly aggressive malignant tumors. We recently reported tumor growth and VM formation of gallbladder cancers through the contribution of the ephrin type a receptor 2 (EphA2)/focal adhesion kinase (FAK)/Paxillin signaling pathways. In this study, we further investigated the anti-VM activity of norcantharidin (NCTD) as a VM inhibitor for gallbladder cancers and the underlying mechanisms. In vivo and in vitro experiments to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…21,25,38 VEcadherin can activate MMPs via the EphA2 signaling pathway. 39 Furthermore, hypoxia-induced Twist1 expression also induces MDA-MB-231 cells to generate more CSCs, which then promote VM channel formationin Matrigel. 25 Hence, hypoxia induced by blocking the VEGF pathway not only directly promotes TNBC tumor invasion but also accelerates VM.…”
Section: Discussionmentioning
confidence: 99%
“…21,25,38 VEcadherin can activate MMPs via the EphA2 signaling pathway. 39 Furthermore, hypoxia-induced Twist1 expression also induces MDA-MB-231 cells to generate more CSCs, which then promote VM channel formationin Matrigel. 25 Hence, hypoxia induced by blocking the VEGF pathway not only directly promotes TNBC tumor invasion but also accelerates VM.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF and phosphoinositide 3-kinase/AKT pathway also exert positive feedback regulation in the process of VM formation [39]. EphA2 is a protein tyrosine kinase receptor commonly expressed in epithelial cells [40], and it contributes to VM formation by mediating the EphA2/FAK/Paxillin pathway[41–44]. In the Wnt/ β -catenin pathway, hypoxic conditions and microRNAs also take part in VM formation [45–47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some reports suggested that FAK participates in VM formation in gallbladder cancer. 35,36 Thus, FAK is probably associated with VM formation through an ITGB1-dependent mechanism(s). Further studies are necessary to elucidate the signaling cascade of ITGB1-mediated VM formation.…”
Section: Fak Signaling Is Triggered By Cell Adhesion and Correlates Withmentioning
confidence: 99%